Предмет: Алгебра, автор: manatt905ow5hv8

Дам 98 баллов. Упростите выражение

Приложения:

Ответы

Автор ответа: NNNLLL54
1

1)\; \; (x^2-1)\Big (\frac{1}{x-1}-\frac{1}{x+1}-1\Big )=(x-1)(x+1)\cdot \frac{x+1-(x-1)-(x^2-1)}{(x-1)(x+1)}=\\\\=x+1-x+1-x^2+1=3-x^2\\\\\\2)\; \; (m+1+\frac{1}{m-1}\Big ):\Big (m-\frac{m^2}{m-1}\Big )=\frac{(m+1)(m-1)+1}{m-1}:\frac{m(m-1)-m^2}{m-1}=\\\\=\frac{m^2-1+1}{m-1}\cdot \frac{m-1}{m^2-m-m^2}=\frac{m^2}{m-1}\cdot \frac{m-1}{-m}=-m

Похожие вопросы
Предмет: Литература, автор: виберник